Prediction of asphaltene precipitation from n-alkane diluted crude oil by using PC-SAFT equation of state. (17th June 2016) - Serajian, A.; Sefti, M. Vafaie; Shadman, M. M.; Zahedi, E.; Veisi, S.; Ahmadi, S.
ABSTRACT: The precipitation tendency of heavy organics such as asphaltene has posed great challenges for petroleum industry, and thus study of asphaltene precipitation amount and formation conditions seems to be necessary. One of the most common approaches for prediction of asphaltene precipitation is using thermodynamic models. In this study a PC-SAFT equation of state (EOS) is used to predict asphaltene precipitation in two Iranian dead oil samples. Asphaltene content is obtained by filtration method of the oil samples diluted with specific concentrations of different normal alkanes. Also liquid-liquid equilibrium is used for characterization of oil sample into one heavy phase (asphaltene) and another light phase (saturates, aromatics, and resin). Calculations show that the developed model is highly sensitive to interaction parameter between oil fractions. Prediction results were improved due to using Chueh-Prausnitz equation. The results indicate good potential of PC-SAFT EOS in the prediction of asphaltene precipitation in crude oil samples diluted with different normal alkanes. The model error is <5% and the model precision is increased by reducing the number of normal alkane carbons.